2023
DOI: 10.1108/jd-03-2023-0044
|View full text |Cite
|
Sign up to set email alerts
|

Online subject searching of humanities PhD students at a Swedish university

Koraljka Golub,
Xu Tan,
Ying-Hsang Liu
et al.

Abstract: PurposeThis exploratory study aims to help contribute to the understanding of online information search behaviour of PhD students from different humanities fields, with a focus on subject searching.Design/methodology/approachThe methodology is based on a semi-structured interview within which the participants are asked to conduct both a controlled search task and a free search task. The sample comprises eight PhD students in several humanities disciplines at Linnaeus University, a medium-sized Swedish universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…There was also a study that compared student perceptions of the Google Scholar interface with the Library Information Retrieval System. The results of this study indicated that the Google Scholar interface was simpler and easier to use than the Library Information Retrieval System (Wu & Chen 2014;Golub et al 2023). Thus, it is not surprising that Google is still the favorite of students when finding information resources.…”
Section: Page14mentioning
confidence: 83%
“…There was also a study that compared student perceptions of the Google Scholar interface with the Library Information Retrieval System. The results of this study indicated that the Google Scholar interface was simpler and easier to use than the Library Information Retrieval System (Wu & Chen 2014;Golub et al 2023). Thus, it is not surprising that Google is still the favorite of students when finding information resources.…”
Section: Page14mentioning
confidence: 83%